ISOLASI SENYAWA ALKALOID DARI TUMBUHAN Cryptocarya bracteolata (LAURACEAE) - Saidi, Nurdin; Morita, Hiroshi; Litaudon, Marc; Mukhtar, Mat Ropi; Awang, Khalijah; Hadi, A. Hamid A. (Jurnal Farmasi Indonesia, 2012)
Isolation of alkaloids from the bark of C. bracteolata Gamb yielded two compounds ofaporphines alkaloid, (+)-Lirioferine and (+)-Bracteoline. The extraction of the bark wascarried out by maceration, and isolation was carried out by column chromatography.Structural elucidation was established through several spectroscopic methods, such as 1DNMR(1H, 13C, DEPT), 2D-NMR (COSY, HMQC, HMBC), UV, IR, MS and comparison withthe published data.ABSTRAKDua senyawa alkaloid jenis aporfin, yaitu (+)-Lirioferin dan (+)-Bracteolin telah diisolasi darikulit batang C. Bracteolata. Ekstraksi senyawa dilakukan menggunakan cara maserasi danisolasi dengan kromatografi kolom. Elusidasi struktur dilakukan dengan berbagai jenisspektroskopi, meliputi 1D-NMR (1H, 13C, DEPT), 2D-NMR (COSY, HMQC, HMBC), UV, IR,EIMS dan perbandingan data senyawa yang sudah dipublikasi sebelumnya.